2006
DOI: 10.2459/01.jcm.0000215275.55144.17
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted thoracoscopic clipping of patent ductus arteriosus: close to the gold standard and minimally invasive competitor of percutaneous techniques

Abstract: The success rate of VATS clipping compares favorably with the thoracotomic approach but without chest wall trauma and it may have a very favorable cost-effective therapeutic balance compared to transcatheter techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 24 publications
2
8
0
1
Order By: Relevance
“…There is a wide variation (0.7-67%) in the recorded incidence of LVCP post PDA ligation, as summarised in Table 4. 3,[7][8][9][10][11][12][13][14][23][24][25][26][27][28][29][30][31] The incidence (31%) of LVCP in the current study is comparable to that reported in the literature. Our study included infants less than 29 weeks gestation and the nasopharyngolaryngoscopy was done only if the infants were deemed symptomatic by the attending clinician.…”
Section: Discussionsupporting
confidence: 80%
“…There is a wide variation (0.7-67%) in the recorded incidence of LVCP post PDA ligation, as summarised in Table 4. 3,[7][8][9][10][11][12][13][14][23][24][25][26][27][28][29][30][31] The incidence (31%) of LVCP in the current study is comparable to that reported in the literature. Our study included infants less than 29 weeks gestation and the nasopharyngolaryngoscopy was done only if the infants were deemed symptomatic by the attending clinician.…”
Section: Discussionsupporting
confidence: 80%
“…Due to the fact that three articles [1113] compared two different cohorts of patients, each cohort was treated as a separate study, therefore 33 studies ( n  = 4887 subjects) were included into this meta-analysis. Specifically, the study by Davis et al [11] contained two groups of patients, one treated by ligation and one by clip method, and thus for the purposes of analysis was considered as two separate studies.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-two studies that satisfied the inclusion criteria were included in the analysis (Fig 1). OCEBM levels of evidence varied from level 3 (9 studies) [9][10][11][14][15][16]20,23,26 to level 4 (23 studies) [6][7][8]12,13,[17][18][19]21,22,24,25,[27][28][29][30][31][32][33][34][35][36][37] ( Table 1). Occurrence of UVFP, type of surgery, patient demographics, and vocal fold assessment are reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…7,8,[10][11][12][13][14][15]17,20,21,24,[27][28][29][30][31][34][35][36][37] The weighted pooled proportion was 8.7% (95% CI, 5.4% to 12.6%) (Fig 3). Heterogeneity analysis measured an I 2 of 81.6% (95% CI, 65.0% to 88.4%).…”
Section: Analysis By Type Of Surgerymentioning
confidence: 99%